Secrets of animal survival. - National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 1983)
Describes the specific physical adaptations of animals to five different types of environments including Arctic and Antarctic, desert, rain forest, savanna, and mountain.
Accompanied by "Classroon activities" folder containing a "Far-out fun" pamphlet (8 p.), 8 duplicating masters, and 8 catalog cards.
Prepared by the Special Publications and School Services Division of the National Geographic Society.
Includes bibliographical references and index.
Keywords: Animal behavior -- Juvenile literature; Adaptation (Physiology) -- Juvenile literature; Animal habitations; Animal behavior; Adaptation (Biology)